Nilai Moral dalam Novel Rindu Karya Tere Liye:Tinjauan Psikologi Sastra Dan Implementasinya DalamPembelajaran Sastra Di SMA - Sari, Dewi Puspita (2016)
Dewi Puspita Sari, Indonesian Department of Education, the Faculty of Education, University of Muhammadiyah Surakarta, 2015, 87 pages. depusa.temebm@gmail.com The purpose of this study was to describe (1) the socio-historical background Tere Liye as the novelist Rindu. (2) a novel structure Rindu works Tere Liye, (3) the moral values contained in the work Rindu novel Tere Liye, (4) the implementation of novel research results Rindu Tere Liye work on learning in high school. This study used a qualitative descriptive approach. Object under investigation is the moral value of the novel Homesick work Tere Liye. Data in the form of phrases, sentences, and paragraphs. Sources of data in the form of novel Homesick work Tere Liye. Data collection techniques in the form of technical literature, see, and record. Data were analyzed using semiotic reading model, the heuristic and hermeneutic reading. The results of the study (1) the socio-historical background Tere Liye has the original name Dervish, born May 21, 1979 in Palembang, South Sumatra, (2) a novel structure Rindu, theme novel Rindu is longing. Flow used is advanced. The main character is Gurutta. Background time in 1938, for nine months. Background place ie from Makassar port to the port of Jeddah. Social background is harmony, wealth, harmony, (3) the moral values contained in the novel Rindu (a) humility embedded in Dale barber, Bonda Upe, Daeng Andipati, and Mbah Kakung, (b) the courage embedded in Ambo Uleng, Daeng Andipati, and Gurutta, (c) independence is embedded in Gurutta, (d) a willingness to take responsibility reflected in captain Phillips, Gurutta, and Ambo Uleng, (e) the honesty reflected in Bonda Upe, Gurutta, and Daeng Andipati, (4) the results of the research can be implemented from several categories, (a) novel Homesick work tere liye entered the stage of generalization, (b) novel Homesick work Tere Liye is reachable group of teen readers, this novel provides depiction that can be used as the psychological development is good for children ages 13-16 years, this novel its contents in accordance with the background of high school students, (c) novel Homesick work Tere Liye, can be implemented in class XI semesters 1 (a), (d) the results of the research as a teaching material in the form of a novel, editing and abstracting text fiction novel, structural analysis, and moral values.